STAGES OF ORGANIZATION OF SCIENTIFIC AND METHODOLOGICAL OBSERVATION IN THE PROFESSIONAL DEVELOPMENT OF THE TEACHER - Ibragimov Alamjon Amrilloyevich (International Journal of Innovations in Engineering Research and Technology, 2021)
The article describes the organization of scientific and methodological monitoring of the professional development of teachers in the process of professional development of public educators, the quality and effectiveness of the implementation of this process in practical training on training modules. The lines are illuminated.